The Implementation of Certain Goods and Services Tax (PBJT) Policy on Hotel Services on Local Original Revenue (PAD) in Bogor Regency - Rahman Wijaya Laksana; Rita Rahmawati; R. Oetje Subagdja (PT. Lembaga Penerbit Penelitian Nusantara, 2026)
This study examines the implementation of the Local Tax on Certain Goods and Services (PBJT) in hotels in Bogor Regency and its impact on Regional Original Revenue (PAD) after Law No. 1 of 2022. Using a quantitative approach based on Edward III’s model, the study analyzes communication, resources, disposition, and bureaucratic structure. Data from 684 respondents were analyzed using multiple linear regression. Results show PBJT significantly increases PAD (R²: 71.7%–76.0%; p < 0.001), with bureaucratic structure and resources as the most influential factors. However, challenges remain, including unclear communication, limited resources, and low taxpayer compliance. Strengthening institutional capacity, improving coordination, and enhancing taxpayer compliance are recommended to optimize PAD.